Neural Stem Cells Differentiated From iPS Cells Spontaneously Regain Pluripotency. (15th September 2014) - Choi, Hyun Woo; Kim, Jong Soo; Choi, Sol; Hong, Yean Ju; Kim, Min Jung; Seo, Han Geuk; Do, Jeong Tae
Abstract: Differentiated somatic cells can be reprogrammed into pluripotent stem cells by transduction of exogenous reprogramming factors. After induced pluripotent stem (iPS) cells are established, exogenous genes are silenced. In the pluripotent state, retroviral genes integrated in the host genome are kept inactive through epigenetic transcriptional regulation. In this study, we tried to determine whether exogenous genes remain silenced or are reactivated upon loss of pluripotency or on differentiation using an in vitro system. We induced differentiation of iPS cells into neural stem cells (NSCs) in vitro; the NSCs appeared morphologically indistinguishable from brain-derived NSCs and stained positive for the NSC markers Nestin and Sox2 . These iPS cell-derived NSCs (iPS-NSCs) were also capable of differentiating into all three neural subtypes. Interestingly, iPS-NSCs spontaneously formed aggregates on long-term culture and showed reactivation of the Oct4 -GFP marker, which was followed by the formation of embryonic stem cell-like colonies. The spontaneously reverted green fluorescent protein (GFP)-positive (iPS-NSC-GFP + ) cells expressed high levels of pluripotency markers ( Oct4 and Nanog ) and formed germline chimeras, indicating that iPS-NSC-GFP + cells had the same pluripotency as the original iPS cells. The reactivation of silenced exogenous genes was tightly correlated with the downregulation of DNA methyltransferases (Dnmts) during differentiation of iPS cells. This phenomenon was not observed in doxycycline-inducible iPS cells, where the reactivation of exogenous genes could be induced only by doxycycline treatment. These results indicate that pluripotency can be regained through reactivation of exogenous genes, which is associated with dynamic change of Dnmt levels during differentiation of iPS cells. Stem Cells 2014;32:2596–2604